ICU care associated with symptoms of depression and posttraumatic stress disorder among family members of patients who die in the ICU - Kross, Erin K; Engelberg, Ruth A; Gries, Cynthia J; Nielsen, Elizabeth L; Zatzick, Douglas; Curtis, J Randall (Chest, 2011)
Psychologic symptoms of posttraumatic stress disorder (PTSD) and depression are relatively common among family members of patients who die in the ICU. The patient-level risk factors for these family symptoms are not well understood but may help to target future interventions. We performed a cohort study of family members of patients who died in the ICU or within 30 h of ICU transfer. Outcomes included self-reported symptoms of PTSD and depression. Predictors included patient demographics and elements of palliative care. Two hundred twenty-six patients had chart abstraction and family questionnaire data. Family members of older patients had lower scores for PTSD (P = .026). Family members that were present at the time of death (P = .021) and family members of patients with early family conferences (P = .012) reported higher symptoms of PTSD. When withdrawal of a ventilator was ordered, family members reported lower symptoms of depression (P = .033). There were no other patient characteristics or elements of palliative care associated with family symptoms. Family members of younger patients and those for whom mechanical ventilation is not withdrawn are at increased risk of psychologic symptoms and may represent an important group for intervention. Increased PTSD symptoms among family members present at the time of death may reflect a closer relationship with the patient or more involvement with the patient's ICU care but also suggests that family should be offered the option of not being present.